2020
DOI: 10.1071/cp19474
|View full text |Cite
|
Sign up to set email alerts
|

Soil and foliar zinc biofortification of broccolini: effects on plant growth and mineral accumulation

Abstract: Millions of people have Zn-deficient diets, so Zn-biofortified crops could prevent such deficiency. The aim of this study was to evaluate the use of agronomic Zn biofortification of broccolini – a new hybrid crop variety derived from a cross between kalian cabbage and broccoli. Plants were grown in pots using a Zn deficient soil. Four fertiliser treatments were tested: (1) control; (2) soil application of 5 mg ZnSO4•7H2O kg–1 soil; (3) foliar application at the early flowering stage of 0.5% (w/v) ZnSO4•7H2O; (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Skrypnik et al (2019) noted that the application of Se to the nutrient solution had a significant effect on the essential oil content in basil leaves compared to foliar application. Some authors suggested that the combined application of Zn, Fe, and Se soil and foliar fertilizers (Gomez-Coronado et al 2016;Rivera-Martin et al 2020) and fertilization with amendments like, i.e., biochar or salicylic acid (Ramzani et al 2016;Smoleń et al 2019) influenced a better efficiency for microelements accumulation in crops compared to when used separately. For example, it was found that Zn fertilization improved Fe concentration in grains (Niyigaba et al 2019).…”
Section: Type Of Applicationmentioning
confidence: 99%
“…Skrypnik et al (2019) noted that the application of Se to the nutrient solution had a significant effect on the essential oil content in basil leaves compared to foliar application. Some authors suggested that the combined application of Zn, Fe, and Se soil and foliar fertilizers (Gomez-Coronado et al 2016;Rivera-Martin et al 2020) and fertilization with amendments like, i.e., biochar or salicylic acid (Ramzani et al 2016;Smoleń et al 2019) influenced a better efficiency for microelements accumulation in crops compared to when used separately. For example, it was found that Zn fertilization improved Fe concentration in grains (Niyigaba et al 2019).…”
Section: Type Of Applicationmentioning
confidence: 99%